(untitled) (Journal of International Studies, 2007)
Because of different origins of culture and various directions of cultural development, people from different territories will have to face up to different environments and suffer from diverse problems, each of which need suitable shape of knowledge for people to survive and develop. According to various cultural types and knowledge shapes, the educational forms for both culture-survival and knowledge-application will be various necessarily. Nomadic culture is the traditional culture of Mongolia. The traditional nomadic culture of Mongolian started from the Mongolian ancestors westward moving in the latter half of 8th century and finalized at the beginning of 13th century when the Mongolian Plateau was unified, the Great Mongol State was founded and an ethnic community was formed. During this period, Mongolia experienced several historical stages from clans, tribes, tribal alliances to the early classed-nations. In the aspect of shape of knowledge, the historical knowledge of tribe, knowledge of Shamanism worship and knowledge of military and the Mongolian characters occupied the main position at that time. Therefore, the relating educational form is necessary to impart and expand all those knowledge.